BNC-Education and the Continuing Education of teachers - Nogueira, Adrinelly Lemes; Borges, Maria Célia (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
In a study on recent teacher formative policies, we highlight the new Curricular Guidelines for Initial Formation of Basic Education Teachers, which establish the Common National Base for Initial Education of Basic Education Teachers (BNC-Education), recently approved on December 19, through Ordinance No. 2,167, which has been disfiguring the teacher formation that has been historically defended. In view of this note, we aim to propose a reflection on the new BNC-Education and its possible impacts on the continuing education of teachers. We carried out a qualitative study and, through a bibliographical research and documentary analysis, we structured the present reflection. Our analysis showed that the continuing education of Basic Education teachers has been negatively impacted by the new resolution, representing setbacks for education in the theoretical-scientific and practical aspects, and also with gains for the educational market assumptions.